Pengaruh Desentralisasi Fiskal dan Belanja Modal Terhadap Ketimpangan Regional di Pulau Sumatera - Sri Dewi Julita Sari; Muhammad Irfan (Universitas Negeri Padang, 2025)
This study investigates the impact of fiscal decentralization and capital expenditure on regional inequality across Sumatra Island. Utilizing panel data from ten provinces over the 2015–2024 period, the analysis employs a Fixed Effect Model (FEM) to control for unobserved heterogeneity among provinces. Regional inequality is measured using the Williamson Index, while fiscal decentralization is proxied by the degree of expenditure-side fiscal decentralization. The empirical results indicate that both fiscal decentralization and capital expenditure exert a negative and statistically significant effect on regional inequality. These findings underscore the critical role of optimizing local revenue (PAD) and prioritizing capital investment in basic infrastructure to foster more equitable regional development across Sumatra Island.